THE EFFECT OF LEARNING TEACHNIQUES AND SELF CONFIDENCE TOWARD TO STUDENTS' SPEAKING SKILL IN INDONESIANDISCUSSION (EXPERIMENTAL STUDY OF THE 17TH NATIONAL SENIOR HIGH SCHOOL STUDENTS PALEMBANG) - Sri Wahyu Indrawati; Emzir Emzir; Ninuk Lustyantie (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The aim of this study was to determine the effect of learning techniques and self confidence of students' speaking skills in Indonesian discussion. This research was conducted on the students of the 107th class of the 17th National Senior High School Palembang in 2017 by using factorial experimental design technique 2 x 2. Type of research conducted is experiment technique analysis which was used Analysis of variance (ANAVA) two ways at level of significance 0,05.The results of this study indicated that mind mapping techniques were more effective than problem-based learning techniques, and then there was an interaction effect betweenStudents' speaking skill in Indonesian discussions by using mind mapping technique and students learning by using problem-based techniques, probability values ​​M_learning (0.795) ˂0.05. The mean value of learning with mind mapping technique is greater than the average value of learning with problem-based technique (84.89) ˂ (80.89).